562. Management and Outcomes of Patients With Acute HIV Infection in an Expanded Testing and Linkage to Care Program. (26th November 2018) - McNulty, Moira C; Schmitt, Jessica; Friedman, Eleanor; Hunt, Bijou; Tobin, Audra; Maheswaran, Anjana Bairavi; Lin, Janet; Novak, Richard; Sha, Beverly; Moswin, Arthur; Rose, Breon; Pitrak, David; et al.
Abstract: Background: Persons with acute HIV infection have high viral loads and are highly infectious compared with those with chronic infection. Rapid linkage to care and initiation of therapy, facilitated by new testing algorithms, allows for immunologic preservation and rapid virologic control, which benefits the individual and decreases transmission events. Methods: We analyzed testing data (2016–2017) from the xTLC Program, a collaborative effort between 13 healthcare centers on the South and West sides of Chicago. For acute HIV infections, we assessed linkage to care, initiation of antiretroviral therapy (ART) and viral suppression across sites. Results: Of 334 new HIV diagnoses in xTLC, 33 (9.9%) had acute infection across six sites (five acute care hospitals/emergency departments, one clinic). Baseline viral load (VL) was 2.19 million copies/mL (IQR 0.47–5.00) and baseline CD4 count was 440.5/µL (IQR 287.5–568.5). Table 1 shows care continuum outcomes for patients with acute HIV infection. Conclusion: Patients with acute HIV infection can be successfully managed in existing programs for HIV screening and linkage to care. The xTLC program had a high linkage to care rate, timely initiation of ART, and relatively quick reduction in viral loads. Our outcomes approach those seen for intensive immediate therapy programs, but without additional costs beyond those of the xTLC program. This will likely create similar public health benefits as dedicated programs for rapid initiation of therapy. Disclosures: B. Hunt, Gilead: supported by Gilead FOCUS grant, Salary. A. Tobin, Gilead: supported by Gilead FOCUS grant, Salary. A. B. Maheswaran, Gilead: supported by Gilead FOCUS grant, Salary. J. Lin, Gilead: Grant Investigator, Grant recipient. R. Novak, Gilead: Scientific Advisor, Consulting fee. Viiv: Scientific Advisor, Consulting fee. Theratech: Scientific Advisor, Consulting fee. B. Sha, Gilead Sciences: Grant Investigator and Investigator, Grant recipient and Research grant. Viiv Healthcare: Investigator, Research grant. D. Pitrak, Gilead: Grant Investigator, Grant recipient and Research grant. N. Glick, Gilead: Grant Investigator and Scientific Advisor, Grant recipient